2011
DOI: 10.1253/circj.cj-10-0881
|View full text |Cite
|
Sign up to set email alerts
|

Angiography Is the Gold Standard and Objective Evidence of Myocardial Ischemia Is Mandatory If Lesion Severity Is Questionable - Indication of PCI for Angiographically Significant Coronary Artery Stenosis Without Objective Evidence of Myocardial Ischemia (Pro) -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp t present, coronary artery disease (CAD) remains the biggest cause of death. While the mortality rate of acute coronary syndrome (ACS) has declined in recent years, mortality due to stable CAD has been unchanged over the last decades. 1 Medical treatment for CAD aims at stabilization of plaque and prevention of progression, as well as prevention of plaque rupture and subsequent future events, while treating the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Although CAG is widely considered the gold standard for the diagnosis of CAD as well as a primary examination for guiding PCI procedures and judging coronary intervention success ( 5 , 27 , 28 ), studies have suggested that its use alone may miss important information. Such studies have claimed that treatment strategies would be modified if the OCT examination was used with or instead of CAG ( 27 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CAG is widely considered the gold standard for the diagnosis of CAD as well as a primary examination for guiding PCI procedures and judging coronary intervention success ( 5 , 27 , 28 ), studies have suggested that its use alone may miss important information. Such studies have claimed that treatment strategies would be modified if the OCT examination was used with or instead of CAG ( 27 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in interventional cardiology have highlighted the importance of a detailed understanding of the tissue characteristics of coronary atherosclerotic lesions, including the identification of plaque stability, estimation of lesion covering, and tearing degree pre- and post-PCI ( 3 , 4 ). Coronary angiography (CAG) has been considered to be the gold standard diagnostic method for CAD and is widely accepted as a firm basis for determining treatment strategies for PCI ( 5 ). However, previous evidence indicated that CAG may not provide accurate images in certain cases and may fail to reflect specific critical characteristics of atherosclerotic lesions or vessel-stent associations in high-risk cases ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional coronary angiography is a gold standard for the diagnosis of coronary artery narrowing but it has a disadvantage of being an invasive procedure with a life threatening complication rate of one per thousand. [11] A study suggested that calcium scores can be used to stratify risk factor in asymptomatic patient and is a strong predictor of predictive information beyond the traditional risk factors in different ethnic group. [2] However, in this study having risk factors did not increase calcium score in most cases so it may be hypothesized that coronary calcium score and traditional risk factors might be independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management and thrombolysis focuses on symptomatic treatment as well as plaque stabilization, prevention of progression of subsequent future events. But revascularization by either PCI or coronary artery bypass grafting (CABG) aims to re-establish coronary artery flow leading to improvement of ischemia and its manifestations [12]. The Urgency of the treatment is based on various pathologic changes in the myocardium following STEMI, which is illustrated in Figure 2.…”
Section: Pathophysiology and Management Of Stemimentioning
confidence: 99%